2015
DOI: 10.1021/jp511969t
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Raman Spectra of C70 Fullerene Carbon Peapods

Abstract: International audienceThis work focuses on the hybrid system between C70 and a carbon nanotube (C70 peapod) where the encapsulated C70 peas and the nanotube pod are bonded through van der Waals interactions. The nonresonant Raman spectra of these nanomaterials were calculated in the framework of the bond-polarizability model combined with the spectral moment method. The optimal configurations of C70 molecules are derived using a convenient Lennard-Jones potential. We find that increasing the nanotube diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…These results indicate that only one type of orientation can exist for a given nanotube and confirm that the C 70 alignment is associated with the geometrical parameters of the nanotube host. Theoretical studies showed that the configuration of C 70 s inside SWCNT depends primarily on tube diameter and does not significantly depend on tube chirality [21,22]. In order to obtain the optimal structure of the C 70 inside the nanotubes, an energy minimization procedure was performed by Fegani et al (for more detail, see reference [21]).…”
Section: Peapodsmentioning
confidence: 99%
See 4 more Smart Citations
“…These results indicate that only one type of orientation can exist for a given nanotube and confirm that the C 70 alignment is associated with the geometrical parameters of the nanotube host. Theoretical studies showed that the configuration of C 70 s inside SWCNT depends primarily on tube diameter and does not significantly depend on tube chirality [21,22]. In order to obtain the optimal structure of the C 70 inside the nanotubes, an energy minimization procedure was performed by Fegani et al (for more detail, see reference [21]).…”
Section: Peapodsmentioning
confidence: 99%
“…Theoretical studies showed that the configuration of C 70 s inside SWCNT depends primarily on tube diameter and does not significantly depend on tube chirality [21,22]. In order to obtain the optimal structure of the C 70 inside the nanotubes, an energy minimization procedure was performed by Fegani et al (for more detail, see reference [21]). The authors found that the C 70 molecules adopt a lying orientation for small SWCNT diameters (below 1.356 nm), whereas a standing orientation is preferred for large diameters (above 1.463 nm).…”
Section: Peapodsmentioning
confidence: 99%
See 3 more Smart Citations